Продуктивність штучних лісових насаджень у підзоні типчаково-ковилових степів - Shevchuk, N.J. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The productivity of the artificial forest planting in souths steppes is studied. It is set that biological productivity of planting depends on culture specie and age of xyliums which accumulate most biomass in third or in fourth agedependent groups. Most indexes of grassy vegetation biomass are characte ristic for the 35–40 years planting.